2018
DOI: 10.1080/15325024.2018.1518772
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a Cancer Bereavement Therapeutic Group

Abstract: This study examined the effectiveness of a novel cancer bereavement group. Twenty-seven participants attended a sixsession cancer bereavement therapeutic group. Data were collected at baseline, intervention completion, and three-month follow-up. Grief intensity and symptoms of posttraumatic stress disorder (PTSD), depression, and anxiety were reduced postintervention, and self-compassion increased. At follow-up, improvement remained for grief, PTSD, and depression. A small quasi-experimental waiting-list compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…The number of required study participants was ascertained to be 60. The previous feasibility study in this area was conducted in about 25–50 cases 19 32–36. Adding the 10 cases for drop-out, we determined 60 as the appropriate target sample size.…”
Section: Methodsmentioning
confidence: 99%
“…The number of required study participants was ascertained to be 60. The previous feasibility study in this area was conducted in about 25–50 cases 19 32–36. Adding the 10 cases for drop-out, we determined 60 as the appropriate target sample size.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies found that PTSD symptoms may develop also after a non-Criterion A event such as infidelity (Roos et al, 2019), childbirth (Cigoli et al, 2006), social trauma (Carleton et al, 2011), bereavement due to expected death (Jerome et al, 2018), discrimination (Wei et al, 2015), cancer (Swartzman, Sani, & Munro, 2017), workplace harassment (Tatar & Yüksel, 2019), or foot-and-mouth disease (Olff et al, 2005). Anders et al (2012) identified a significant effect between relational traumas (e.g., breakup, rejection, and cheating) and PTSD symptoms and found no differences between A1 and non-A1 relational events in terms of outcome.…”
Section: Non-criterion a Events Leading To Ptsd Symptomsmentioning
confidence: 99%